Pengaruh Edukasi Metode Demonstrasi Pembuatan MP-Asi Terhadap Pengetahuan Dan Keterampilan Ibu Balita Stunting Di Puskesmas Teruwai - Yuli Laraeni; Rilia Januarini; Aladhiana Cahyaningrum; Yopi Harwinanda Ardesa (Journal of Innovation Research and Knowledge, 2026)
Stunting remains aserious public health issue, in Indonesia including in the working area of Teruwai Public Health. One of the contributing factors to stunting is the inappropriate provision of complementary feeding (MP- ASI). Improving mothers' skills in preparing MP-ASI is a key step in preventing stunting. One effort that can be made is providing education that encourages increased knowledge and skills among mothers of toddlers in preparing appropriate MP-ASI to prevent stunting in villages within the Puskesmas Teruwai area. This study aims to determine the effect of education using the demonstration method on increasing the knowledge and skills of mothers of stunted toddlers aged 6–23 months in providing MP-ASI. This research used a quasi-experimental design with a pretest- posttest control group approach. The sample consisted of 46 mothers of stunted toddlers, divided into a treatment group (26 participants) and a control group (20 participants), selected through total sampling. The analysis showed a significant effect on the mothers' knowledge and skills after being given education through the demonstration method, with a p-value < 0.05 in both the treatment and control groups. There is a significant effect of education using the demonstration method on the knowledge and skills of mothers of stunted toddlers in Sukadana and Pengengat Villages, within the working area of Puskesmas Teruwai, highlighting its importance as an educational strategy to improve complementary feeding practices.